Study of Heavy Metals and Microbial Communities in Contaminated Sediments Along an Urban Estuary - Yi, Jun; Lo, Linus Shing Him; Liu, Hongbin; Qian, Pei-Yuan; Cheng, Jinping (Frontiers in Marine Science, 2021)
Estuarine sediments are increasingly contaminated by heavy metals as a result of urbanization and human activities. Continuous multi-heavy metal accumulation in the ecosystem can provoke new effects on top of the complex environmental interactions already present in estuarine ecosystems. It is important to study their integrated influence on imperative microbial communities to reflect on the environmental and ecological risks they may impose. Inductively coupled plasma optical emission spectroscopy analysis for five metals Cd, Cr, Cu, Pb and Zn showed that Cr and Cu concentrations in intertidal sediments of the urbanized Yangtze River estuary in China have consistently exceeded respective threshold effect concentration levels. The geo-accumulation and potential ecological risk index results of the five metals showed that all sampling sites were weakly to moderately polluted, and at considerable to high ecological risk, respectively. Redundancy and correlation analyses showed that Zn followed by Cr in the ecosystem were explanatory of the shifts in recorded microbial community structures. However, the spatial variation in metal concentrations did not correspond to the selection of metal resistance genes. Unlike many other dominant bacterial taxa, most of the sulfate-reducing bacteria and associated sulfate respiration as the dominant microbially-contributed ecological function were found to negatively correlate with Zn and total heavy metal pollution. Zn concentration was proposed to be a potent indicator for heavy metal pollution-associated microbial community compositional shifts under urbanized estuarine conditions. The associations between heavy metals and estuarine microbial communities in this study demonstrate the influence of heavy metals on microbial community structure and adaptations that is often overshadowed by environmental factors (i.e. salinity and nutrients).